Amide-functionalized pillar[5]arenes as a novel class of macrocyclic receptors for the sensing of H2PO4− anion. Issue 84 (3rd October 2016) - Yakimova, L. S.; Shurpik, D. N.; Stoikov, I. I.
Abstract : First, the "binding strength–selectivity" relationship has been decided for pillar[5]arene/anion systems. Abstract : A novel class of amide-functionalized pillar[5]arenes, that is, alkyl and aryl amide derivatives, has been synthesized. Highly selective binding of the dihydrogen phosphate anion over a range of anions by the new synthetic receptors is reported. First, the "binding strength–selectivity" relationship has been decided for the pillar[5]arene/anion systems.